Alliance insurance companies with the banks to promote insurance services (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Insurance companies seeking to develop programs to promote and market their services and to increase its customer through the use of modern technical marketing and reduce its dependence on agents and take advantage of work of the banks by alliances with them and including reinforcing get the parties to competitive advantages in the financial market , the insurance services intangible service stops marketed over the insurance awareness and   requires exceptional promotional efforts.                                                                    This research represents an attempt towards the possibility of benefiting from Arab experiences and to reach an acceptable proposal on a codified alliance between insurance companies and Iraqi banks which aims to develop a simplified work contexts for the promotion and sale of various insurance policies through bank branches with reference to the services and mutual needs between the two sectors.